The Role of Teachers’ Grit and Motivation in Self-Directed Professional Development - Lan, Yuling (Frontiers in Psychology, 2022)
Through English language teaching (ELT), educator professional development is an interesting and significant subject due to the fact it is in the interest of the educators’ career to make sure that its participants perform consistently with the highest degrees of agreed criteria. Correspondingly, educators mostly state a willingness to enhance their own education that allows them to enhance learners’ knowledge and consistent with the advent of the information-based community, the self-directed learning is vital for the employees. The self-directed professional development (PD) method is considered one option to improve vocational educators’ skills to improve their professionalism, learning development, and school development. Within the learning procedure, self-directed PD has used the rules of learning that are covered within the rules of individual teaching and the mental traits and ideas including motivation and grit that could have a mediating function in this area. Grit is critical within English language educator PD and improving it within educator PD means modeling it as a determinant of the learners’ success. In addition, comprehending motivation is vital for everybody intending to reduce expenses for PD, motivate employees, or be self-directed in their learning about the job. The purpose of the present literature review is to examine the function of such constructs in self-directed PD which is considered a great dimension of educator quality. Briefly, many applications are suggested for the scholastic beneficiaries.